Quantification of the Impact of Endometriosis Symptoms on Health Related Quality of Life and Work Productivity - Fourquet, Jessica (2011)
OBJECTIVE: To quantify the impact of endometriosis-related symptoms on physical and mental health status, health-related quality of life (HRQoL), and work-related aspects (absenteeism, presenteeism, work productivity, activity impairment). DESIGN: Cross-sectional quantitative study. SETTING: Academic and research institution. PATIENT(S): Women (n=193) with self-reported surgically diagnosed endometriosis from the Endometriosis Patient Registry at Ponce School of Medicine and Health Sciences (PSMHS). INTERVENTION(S): Patients completed an anonymous questionnaire divided into three sections consisting of questions from the Patient Health Survey (SF-12®), the Endometriosis Health Profile (EHP-5), and the Work Productivity and Activity Impairment Survey (WPAI). MAIN OUTCOME MEASURE(S): Impact of endometriosis symptoms on physical and mental health status, health-related quality of life (HRQoL), absenteeism, presenteeism, work productivity and activity impairment was quantified. RESULTS: Patients had SF-12 scores denoting significant disability in the phyisical and mental health components. They also reported an average of 7.41 hrs (approximately one working day) of work time loss during the week the symptoms are worse. In addition, WPAI scores show high impact on work-related domains: 13% of average loss in work time (absenteeism), 65% of their work was impaired (presenteeism), 64% loss in efficiency levels (work productivity loss), and 60% of daily activities perturbed (activity impairment). CONCLUSION: Endometriosis symptoms such as chronic, incapacitating pelvic pain and infertility negatively and substantially impact the physical and mental health status, HRQoL, and productivity at work of patients with endometriosis.